External exposome and incident asthma across the life course in 14 European cohorts: a prospective analysis within the EXPANSE project - Yu, Zhebin; Kress, Sara; Blay, Natalia; Gregor, Petr; Kukk, Hanna-Maria; Leskien, Miriam; Majewska, Renata; Oosterwegel, Max J; Szabó, Daniel; Ten Have, Margreet; Klánová, Jana; Mikeš, Ondřej; et al. (The Lancet regional health. Europe, 2025)
BACKGROUND: The joint impact of exposure to multiple urban environmental factors on asthma remains unclear. METHODS: We analysed data from 14 European cohorts to assess the impact of the urban exposome on asthma incidence across the life course. We linked three external exposome domains (air pollution, built environment, ambient temperature) to the participants' home addresses at baseline. We performed k-means clustering within each domain and assessed associations of clusters with asthma adjusting for potentially relevant covariates in cohort-specific analyses, with subsequent separate meta-analyses for birth and adult cohorts. An environmental risk score using a coefficient-weighted sum approach was used to assess the impact of combining the three domains. FINDINGS: A total of 7428 incident asthma cases were identified among 349,037 participants (from birth up to age 70+). Overall, we observed higher risks of asthma for clusters characterized by high particulate matter and nitrogen dioxide exposure in adults (ORmeta = 1.13, 95%CI:1.01-1.25), and clusters characterized by high built-up area and low levels of greenness in both children and adults (ORmeta = 1.36, 95%CI: 1.14-1.64 for birth cohorts and ORmeta = 1.15, 95%CI: 1.03-1.28 for adult cohorts, respectively). The joint exposure using the environment risk score combining the three domains was consistently associated with higher risks of incident asthma (ORmeta = 1.13, 95%CI: 1.07-1.20 for birth cohorts, ORmeta = 1.15, 95%CI: 1.10-1.20 for adult cohorts per 20% increase). On average 11.6% of the incident asthma cases could be attributed to environmental risk score above cohort-specific median levels. INTERPRETATION: Multiple environmental exposures jointly contribute to incident asthma risk across the life course. Urban planning accounting for these factors may help mitigate asthma development. FUNDING: This study was funded by the European Union's Horizon 2020 research and innovation program under agreement No 874627 (EXPANSE).
Keywords: Exposome; Cohort; Life course; Asthma